"Live" Together with You: Livestream Views Mitigate the Effects of Loneliness on Well-being. Issue 4 (8th August 2021) - Goh, Zhang Hao; Tandoc, Edson C.; Ng, Bin
ABSTRACT: Most social networking sites today have integrated livestreaming functions into their platforms. Studies have acknowledged how social media use (i.e., social networking) can mitigate the effects of loneliness, but due attention has yet to be given to the consumption of livestream content. Using national survey data in Singapore ( N = 1, 606), this study demonstrates that livestream viewing positively influences individuals' well-being. Notably, the frequency of livestream viewing moderates the negative effects of loneliness on the viewers' psychological, social, and emotional well-being. Livestream viewing can be a short-term interventive solution to mitigate the effects of loneliness.